Bendamustine: a new view on treatment of chronic lymphocytic leukemia - Ye. A. Nikitin (Онкогематология)
Chronic lymphocytic leukemia (CLL) is the most frequent leukemia type in adults. Despite significant achievements in therapy of this disease in young adults, treatment of elderly patients represents the problem, first of all, because of the unsatisfactory acceptability of the regimens containing purine analogues. The new drug – ribomustin – combining properties of alkylating agents and purine analogues is registered in 2010 in Russia. The major advantage of ribomustin is its low toxicity. In several researches it is shown, that ribomustin is effective both in relapse and as front line therapy in CLL patients. Results of clinical studies of ribomustin in CLL patients are discussed in the given review.